SPECIFIC ROLE OF IL-1Β IN URIC ACID-RELATED INFLAMMATION : A NARRATIVE REVIEW - Rona Hawa Kamilah; Salni; Ziske Maritska; Fatmawati (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Inflammatory conditions in hyperuricemia are caused by monosodium urate crystals that induce the release of IL-1β, marking a crucial milestone in the pathogenesis of hyperuricemia. Several studies have linked the relationship between serum uric acid levels and the release of IL-1β. IL-1β plays a key role in the pathogenesis of gout. The IL-1β signaling is currently considered an initiating event that triggers uric acid inflammation and promotes the recruitment of a large number of neutrophils to the inflammatory site. Neutrophil activation caused by crystals results in the inhibition of apoptosis, degranulation, the release of reactive oxygen species (ROS), TNF-α, IL-1β, and PGE2, as well as the formation of extracellular neutrophil tissue, further reinforcing the inflammatory process. Recent research indicates that hyperuricemia patients have significantly higher levels of IL-1β. Other studies suggest that elevated IL-1β levels correlate with a more severe anatomical pathology in the joint tissues of rat ankles, including synovial hyperplasia, cartilage damage, and bone erosion.